Application of the auditory kinesthetic visualization (VAK) model towards the ability to mathematical conceptual understanding - Putri Amalia Harahap; Rivdya Eliza; Fitria Mardika; Abderrahim El Amrani; Elsi Fitria (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
This research is motivated by the low level of comprehension of mathematical concepts among seventh-grade students at SMPN 1 2×11 Enam Lingkung. One cause is that the learning model used has not improved students' conceptual understanding. The effort was to apply the Visual-Auditory-Kinesthetic (VAK) learning model. The objectives of this study are: To determine the significant difference in the average mathematical concept comprehension abilities of students between before and after the implementation of the VAK model, To determine the increase in mathematical concept comprehension abilities of students taught with the VAK model compared to students taught using the expository model, To analyze significant differences in mathematical concept comprehension abilities between classes using the VAK model and classes using the expository model. The study showed that the paired-sample t-test for the experimental class yielded a Sig. value of 0.000 < 0.05, so there was a significant increase in mathematical concept understanding between before and after the implementation of the VAK model, The average N-gain score of the experimental class (VAK model) was 0.7145 (High category), higher than the control class (expository model) of 0.5556 (Medium category), which indicates that the VAK model is more effective in improving mathematical concept understanding, The results of the independent t-test t-count > t-table (2.031 > 1.670), which means there is a significant difference in the ability to understand mathematical concepts between students taught with the VAK model compared to the expository model. Thus, the application of the VAK learning model has a positive and significant influence on students' ability to understand mathematical concepts at SMPN 1 2×11 Enam Lingkung.